The physical demands of elite English rugby union - Roberts, S. P.; Trewartha, G.; Higgitt, R. J.; El-Abd, J.; Stokes, K. A. (Journal of Sports Sciences, 2008)
The aim of this study was to assess the physical demands of elite English rugby union match-play. Player movements were captured by five distributed video cameras and then reconstructed on a two-dimensional plane representing the pitch. Movements based on speeds were categorized as standing, walking, jogging, and medium-intensity running (low-intensity activity), and high-intensity running, sprinting, and static exertion (scrummaging, rucking, mauling, and tackling) (high-intensity activity). Position groups were defined as forwards (tight and loose) and backs (inside and outside). Backs travelled more total distance than forwards (6127 m, s = 724 vs. 5581 m, s = 692; P < 0.05) and greater distances in walking (2351 m, s = 287 vs. 1928 m, s = 2342; P < 0.001) and high-intensity running (448 m, s = 149 vs. 298 m, s = 107; P < 0.05). Forwards performed more high-intensity activity than backs (9:09 min:s, s = 1:39 vs. 3:04 min:s, s = 1:01; P < 0.001), which was attributable to more time spent in static exertion (7:56 min:s, s = 1:56 vs. 1:18 min:s, s = 0:30; P < 0.001), although backs spent more time in high-intensity running (0:52 min:s, s = 0:19 vs. 1:19 min:s, s = 0:26; P = 0.004). Players travelled a greater distance in the first 10 min compared with 50-60 and 70-80 min, but there was no difference in the amount of high-intensity activity performed during consecutive 10-min periods during match-play. These results show the differing physical demands between forwards and backs with no evident deterioration in high-intensity activity performed during match-play.